2011
DOI: 10.1177/0309132511426606
|View full text |Cite
|
Sign up to set email alerts
|

Geographies of friendships

Abstract: Friendships are an important part of what makes us, and our geographies of various kinds, human. We consider how geographers can contribute to efforts to afford friendship greater prominence in the social sciences. The main part of the article considers three strands of work on friendship that push the boundaries of research in human geography: (1) geographies of affect/emotion and the ontological construction of the human; (2) children’s and young people’s geographies and the (re)production of social ordering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 51 publications
1
117
0
4
Order By: Relevance
“…These socio-spatial attachments, parallel to those identified by Bartos (2012Bartos ( , 2013; see also Bunnell et al, 2012 on friendship) with children of approximately the same age in rural New…”
Section: The Shared and Subjective Homesupporting
confidence: 57%
See 1 more Smart Citation
“…These socio-spatial attachments, parallel to those identified by Bartos (2012Bartos ( , 2013; see also Bunnell et al, 2012 on friendship) with children of approximately the same age in rural New…”
Section: The Shared and Subjective Homesupporting
confidence: 57%
“…Marshall (2013) suggests affectivity as one key aspect in analyzing these engagements (also Dyck, 2005;Muños González, 2005), and Bartos (2012Bartos ( , 2013 points to the significance of enmeshed intergenerational and peer relations (also Vanderbeck, 2007;Bosco, 2010;Bunnell et al 2012;Kallio, 2014b). In my study I have found both insights relevant, which becomes apparent in the following analysis where I have selected the case of Milla as being illustrative of the particularity of familial subjectivity and spatial attachments.…”
Section: The Shared and Subjective Homementioning
confidence: 99%
“…Furthermore, in our follow-up meetings and animation workshop sessions with this group after NCS had finished, it became clear that some friendships (and romantic relationships) had strengthened, while others had ended. Overall these geographies of friendship (Bunnell et al 2012) reveal the everyday and ordinary encounters of young people at this stage in the lifecourse, and yet, it is important to remember that these encounters were originally set in motion by the manufactured and engineered programme designed within government and policy circles, as outlined earlier in this paper. This context does not make these friendships and encounters any less powerful, meaningful or valid, but rather, it demonstrates that not all encounters are haphazard chance meetings: these were orchestrated by the state.…”
Section: Engineering and Manufacturing Social MIXmentioning
confidence: 90%
“…When such suspicion resonates as fear in the 'collective unconscious' (Amin, 2012: 63) bodies of colour become 'stress points' (Ahmed, 2007: 160), and the opportunities for fleeting encounters and inter-ethnic/inter-racial friendships in public spaces of the city are limited. Bunnell et al (2012), in their review of geographies of friendship, regret that although emotion and affect enhance understandings of social and cultural life in cities, there is little in-depth research. This can be attributed to the lack of productive engagement between geographies of affect that draw on non-representational theoretical approaches and emotional geographies that draw on feminist approaches (Colls, 2012;Kobayashi et al, 2011;Pile, 2010).…”
Section: Introductionmentioning
confidence: 99%